What’s Right and Wrong in Preclinical Science: A Matter of Principled Investigation - Smith, Laura N. (Frontiers in Behavioral Neuroscience, 2022)
The discovery of efficacious treatment options for neuropsychiatric conditions is a process that remains in jeopardy. Contributing to the failure of clinical trials, a strong positive bias exists in the reported results of preclinical studies, including in the field of neuroscience. However, despite clear recognition of major factors that lead to bias, efforts to address them have not made much meaningful change, receiving inadequate attention from the scientific community. In truth, little real-world value is currently attached to efforts made to oppose positive bias, and instead—partially driven by competitive conditions—the opposite has become true. Since pressures throughout our system of scientific discovery, particularly those tied to definitions of individual success, hold these damaging practices firmly in place, we urgently need to make changes to the system itself. Such a transformation should include a pivot away from explicit or tacit requirements for statistical significance and clean narratives, particularly in publishing, and promotion of a priori power calculations as the determinant of final sample size. These systemic changes must be reinforced and upheld in responsible decisions made by individual scientists concerning the planning, analysis, and presentation of their own research.